Disaster Preparedness for Seniors 2014
DOI: 10.1007/978-1-4939-0665-9_21
|View full text |Cite
|
Sign up to set email alerts
|

Mental Health Consequences of Disaster Exposure in Older Adults

Abstract: Older adults represent the fastest growing demographic of the United States population. However, the elderly are insuffi ciently represented in studies examining the mental health impact of natural and man-made disasters. Social, cultural, and economic variables infl uence disaster-related mental health sequelae with a higher risk for morbidity and mortality among older adults due to physiologic factors, associated cognitive underpinnings, and chronic disease burden. Post-disaster mental health symptoms in eld… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 79 publications
0
8
0
1
Order By: Relevance
“…Although the short-term effect of the disasters on the physical well-being of older adults has been largely studied and proven that they are more vulnerable because of decreased sensory awareness, physical impairment, chronic medical conditions, and socioeconomic limitations experienced by many of the elderly,57 conclusions about the long-term psychological effects of natural disasters on older adults have been inconclusive. Some previous studies reported that the elderly are more likely vulnerable to psychological problems 4,8,9. However, other studies found that the elderly are less vulnerable to psychological impacts of disasters compared to younger survivors 1012…”
Section: Introductionmentioning
confidence: 97%
“…Although the short-term effect of the disasters on the physical well-being of older adults has been largely studied and proven that they are more vulnerable because of decreased sensory awareness, physical impairment, chronic medical conditions, and socioeconomic limitations experienced by many of the elderly,57 conclusions about the long-term psychological effects of natural disasters on older adults have been inconclusive. Some previous studies reported that the elderly are more likely vulnerable to psychological problems 4,8,9. However, other studies found that the elderly are less vulnerable to psychological impacts of disasters compared to younger survivors 1012…”
Section: Introductionmentioning
confidence: 97%
“…2 According to a recent publication on post-disaster outcomes among older persons, researchers found higher morbidity varied with the type of disaster as well as with comorbidities, low social support, need for prescription medications, hearing and visual impairments, impaired mobility, and cognitive deficits. 3,4 Age-related vulnerabilities represent a matrix of challenges for persons negotiating the given disaster, as well as for the agencies bearing legal and moral responsibility for individuals' well-being.…”
mentioning
confidence: 99%
“…[ 42 , 43 ]. Further, the lower age limit of older adults is not consistent in literature, ranging from 60 to 75 years old, potentially limiting comparisons [ 34 ]. Besides, chronological age does not necessarily equate to ‘biological age’, and thus capacity rather than age is a better measure of individual ability [ 44 ].…”
Section: Background: Older Adults Disaster Vulnerability and Risk Cmentioning
confidence: 99%
“…Moreover, research needs to expose the heterogeneity of vulnerability and capacities within older and retired populations to inform more comprehensive risk communication and DRR strategies. DRR approaches need to see beyond vulnerabilities and better-accommodate and value the resilience capacities of older adults, such as mental coping abilities formed through previous experiences of disaster or adversity [ 33 , 34 ].…”
Section: Introductionmentioning
confidence: 99%